2014
DOI: 10.1016/j.molbiopara.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and putative substrate identification for the Entamoeba histolytica low molecular weight tyrosine phosphatase

Abstract: Entamoeba histolytica is a eukaryotic intestinal parasite of humans, and is endemic in developing countries. We have characterized the E. histolytica putative low molecular weight protein tyrosine phosphatase (LMW-PTP). The structure for this amebic tyrosine phosphatase was solved, showing the ligand-induced conformational changes necessary for binding of substrate. In amebae, it was expressed at low but detectable levels as detected by immunoprecipitation followed by immunoblotting. A mutant LMW-PTP protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Synechocystis ’ Wzb was shown to be more closely related to the LMW‐PTP of the unicellular eukaryote E. histolytica than of the LMW‐PTPs of other bacteria (Supporting Information Figure S11). Likewise, a three dimensional protein structure alignment revealed that the structure of Wzb is highly identical to that of the other LMW‐PTPs, being more closely related to that of E. histolytica (PDB entry 3ido) (Linford et al, ), followed by S. aureus (Gram‐positive; PDB entry 3rof) (Vega et al, ) and E. coli (Gram‐negative; PDB entry 2wja) (Hagelueken, Huang, Mainprize, Whitfield, & Naismith, ), with root mean square deviation (RMSD) values (Å) of 1.04, 1.37, and 1.54, respectively, and an average of 95 superimposable residues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synechocystis ’ Wzb was shown to be more closely related to the LMW‐PTP of the unicellular eukaryote E. histolytica than of the LMW‐PTPs of other bacteria (Supporting Information Figure S11). Likewise, a three dimensional protein structure alignment revealed that the structure of Wzb is highly identical to that of the other LMW‐PTPs, being more closely related to that of E. histolytica (PDB entry 3ido) (Linford et al, ), followed by S. aureus (Gram‐positive; PDB entry 3rof) (Vega et al, ) and E. coli (Gram‐negative; PDB entry 2wja) (Hagelueken, Huang, Mainprize, Whitfield, & Naismith, ), with root mean square deviation (RMSD) values (Å) of 1.04, 1.37, and 1.54, respectively, and an average of 95 superimposable residues.…”
Section: Resultsmentioning
confidence: 99%
“…While the first tyrosine usually interacts with the aromatic ring of the substrate, being crucial for the interaction between LMW-PTPs and the BY-kinases (Lescop et al, 2006;Standish & Morona, 2014), the second tyrosine seems to play a role in substrate specificity (Bucciantini et al, 1999;Raugei, Ramponi, & Chiarugi, 2002). (b) Synechocystis' Wzb possesses an aromatic residue-histidine (H45)-in the catalytic site instead of the hydrophobic leucine that occupies this position in most prokaryotic LMW-PTPs (Lescop et al, 2006;Linford et al, 2014). Based on these characteristics, Synechocystis Wzb can be classified as a class I or eukaryotic-like LMW-PTP and is therefore likely to present a substrate recognition mechanism different from that of E. coli Wzb, a class II or prokaryotic-like LMW-PTPs (Lescop et al, 2006 Wzb acts, provides some insights into these differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a large number of these have different structures that are dependent on their crystal form or ligand. Using the FATCAT algorithm operating in rigid mode, we found that the structures of phosphatases from Vibrio cholera O395 (PDB: 4LRQ 52 ), Entamoeba histolytica (PDB: 3IDO 53 ), S. aureus (PDB: 3ROF 54 ), Thermus thermophilus HB8 (PDB: 2CWD ), and arginine phosphatases from Erwinia amylovora (PDB: 4D74 55 ) and Geobacillus stearothermophilus (PDB: 4PIC ) shared the highest structural similarity. Next, we performed searches on PDBeFold by using chain A of the Mtb PtpA structure as a query (PDB: 1U2P 56 ); we found 19 top hits with alignments ( Figure S19 ) sharing 27%–42% sequence identity and with an RMSD of Cα atomic coordinates varying from 1.23 to 1.66 Å.…”
Section: Resultsmentioning
confidence: 99%
“… 59 Nevertheless, the observation of a conserved water network is not observed in all homologous PTPs, given that in some X-ray structures these water molecules are most likely displaced by ligands found within the active site. 52 , 53 , 54
Figure 4 The Catalytic Pocket Is Highly Conserved among the Protein Phosphatase Family (A) Superposition of selected active-site residues and waters of PtpA from M. tuberculosis (PDB: 1U2P ) in gray, YwlE arginine phosphatase from G. stearothermophilus (PDB: 4PIC ) in yellow, tyrosine phosphatase AmsI from E. amylovora (PDB: 4D74 ) in cyan, and TT1001 protein from T. thermophilus HB8 (PDB: 2CWD ) in gray. (B) The active site from the Mtb PtpA crystal structure.
…”
Section: Resultsmentioning
confidence: 99%